Bizancio y sus circunstancias: la evolución de la ideología imperial en contacto con las culturas de su entorno (Minerva, 2019)
The Byzantine imperial ideology is not only a subject of study in fields like the so-called Caesaropapism,the emperor’s inner legitimacy or the court ceremonial, but also depends on the foreing policy of the Empire, which underwent many changes throughout its millenary history. This article surveys the reigns of Justinian I (518/527-565), Constantine VII Porphyrogenitus (912-959) and Manuel II Palaeologus (1391-1425) and stresses the differences between each other from the point of view of the imperial identity.